Meandry i paradoksy międzywojennej cenzury filmowej w Polsce - HENDRYKOWSKA, MAŁGORZATA (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2016)
Meanders and paradoxes of interwar fi lm censorship in Poland The article concerns film censorship in Poland in the interwar period. The first detailed rules on censorship appeared in February 1919. Due to the small level of film production, these provisions related primarily to distribution and screenings. The detailed instructions for censors from 1920 cited in the text contain a long list of prohibitions concerning the presentation of scenes and images “contrary to law and public morality.” In practice, film was subject to political, moral, military, religious, and also artistic censorship. The article presents the ways to circumvent censorship guidelines used by distributors and cinema owners, as well as a critical evaluation of the activities of this institution in the eyes of film publicists.